Yield Components and Productivity of SINHAS 1 Maize on the Application of Different Types and Spraying Frequency of Biofertilizer - Rusnadi Padjung; Muh Farid BDR; Rinaldi Syahrir; Muhammad Fuad Anshori; Ifayanti Ridwan (Universitas Sembilanbelas November Kolaka, 2021)
The purpose of this study was to determine the effect of biofertilizer application based on the types and spraying frequencies on the yield components of maize variety SINHAS 1. The research was conducted in Tarowang Village, Galesong Selatan District, Takalar Regency from August to November 2020. Three types of biofertilizer were used applied in five different frequencies of spraying. The study employed a split plot design with types of biofertilizer as the main plot and application frequencies as the sub plots. The research was repeated 3 times, resulted in a total of 45 experimental units. The maize variety used was SINHAS 1 and observations were made on the yield components of the ear height, wet weight of peeled cobs, ear length and diameter, percentage of seed yield, weight of 1000 seeds at 15% moisture content, and productivity. The results shows that the frequency of biofertilizer application had more dominant effect than the type of biofertilizer. The type of biofertilizer used has relatively the same role in the growth of the yield components of SINHAS 1 corn. Based on the results, it is recommended to apply the biofertilizer in four times in fertilizing the SINHAS 1 maize crop